Aplikasi Berbagai Macam Sumber Pupuk Nitrogen Terhadap Hasil dan Kualitas Dua Varietas Tanaman Kentang (Solanum tuberosum L.) - rifdha hasna' rohadatul aisy; Anis Rosyidah; Indiyah Muwarni (AGRONISMA, 2021)
Nitrogen nutrients have an important role in the process of photosynthesis which functions as a form of leaf chlorophyll. Sufficient chlorophyll in plant leaves results in the photosynthesis process went well, so that the results can be translocated to the tuber. Potato development in the highlands have a problem of limited land area and quality seeds. The purpose of this study was to determine the response of ZA and Urea fertilizer application to the yield and quality of two potato plant varieties (Solanum tuberosum L.) and to obtain a source of N fertilizer and a potato variety (Solanum tuberosum L.) that gave high yields and quality. The experiment was conducted in Sumberejo Village – Batu City at an altitude of 690 masl. Factorial Randomized Block Design consisting of four treatments and six replications. Treatment of nitrogen sources and potato varieties were as follows: S1V1 (ZA fertilizer and Medians variety), S1V2 (ZA fertilizer and Atlantic variety), S2V1 (Urea fertilizer and Medians variety), and S2V2 (Urea fertilizer and Atlantic variety). The results showed that there was an interaction between the parameters of observing fresh weight of tan-1 tuber, fresh weight of tuber ha-1, tuber grade > 60 grams, and vitamin C. The combination of ZA fertilizer treatment and Medians variety gave better potato crop yields with fresh weight of tan-1 of 710.88 grams and fresh weight ha-1 of 37.51 tons. Sources of Urea fertilizer and Medians varieties provide better potato crop quality